Using trade wind to sail in the clouds - De Barros M. (2011)
Cloud computing services provide a new way of deploying applications over the Internet, as well a prominent approach for creating more scalable systems. Usually, exploration of cloud computing resources relies on a regular programming paradigm, depending on adjustments to deal with details inherent to the cloud provider's side that would preferably be transparent. Thus, the complexity of developing applications that fully explore the cloud provider capabilities can increase dramatically according to the features made available. This paper presents Trade Wind (T-Wind), a PaaS (Platform as a Service) solution that provides enhanced features for service providers who want to use cloud services without the need of knowing low level operational details about the cloud. The T-Wind core idea is to empower service providers with a set of features configurable using high level parameters, allowing them to optimize their services as well as to define the cloud behaviors in terms of resource usage and cost. Additionally, the cloud provider in which the T-Wind solution is available can also optimize its resource usage according to its necessities or business rules. First, we present a review of the concepts of cloud computing and its requirements. We then discuss an example of a provider who wants to offer a video streaming service using T-Wind and how T-Wind could be used as a solution to explore the cloud resources in an optimized way.